2019
DOI: 10.1113/ep087127
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to glycated proteins reduces cardiomyocyte contractile capacity

Abstract: New Findings What is the central question of this study?Does acute exposure to high molecular weight advanced glycation end products (HMW‐AGEs) alter cardiomyocyte contractile function? What is the main finding and its importance?Ventricular cardiomyocytes display reduced Ca2+ influx, resulting in reduced contractile capacity, after acute exposure to HMW‐AGEs, independent of activation of their receptor. Given that HMW‐AGEs are abundantly present in our Western diet, a better understanding of underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, it has been shown that AGEs have an important role in the pathophysiology of different complications of diabetes mellitus, e.g., cardiomyopathy, retinopathy, neuropathy, and nephropathy [26]. Additionally, in cardiovascular diseases [27], Alzheimer's disease, and cancer, AGEs have been proven to display a causative role [28]. They can accumulate throughout the body in various tissues such as in the heart [29], blood vessels [30], lungs [31], and adipose tissue [32], exerting long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that AGEs have an important role in the pathophysiology of different complications of diabetes mellitus, e.g., cardiomyopathy, retinopathy, neuropathy, and nephropathy [26]. Additionally, in cardiovascular diseases [27], Alzheimer's disease, and cancer, AGEs have been proven to display a causative role [28]. They can accumulate throughout the body in various tissues such as in the heart [29], blood vessels [30], lungs [31], and adipose tissue [32], exerting long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Whether HMW-AGEs strengthen contraction by disturbing downstream α1 adrenergic signaling factors like phospholipase C, inositol trisphosphate or calcium deserves further investigation. Results from our research group demonstrated that HMW-AGEs indeed disturb calcium homeostasis in cardiomyocytes 34 . HMW-AGEs possibly disturb calcium homeostasis in endothelial or vascular smooth muscle cells as well, which has been shown before following acute exposure to the AGEs precursor methylglyoxal 32 , 35 .…”
Section: Discussionmentioning
confidence: 89%
“…After six weeks of daily injections, conventional echocardiographic images were obtained in rats anesthetized via inhalation with 3% isoflurane supplemented with oxygen as described previously [16] and invasive hemodynamic measurements were performed. Finally, the heart was harvested and left ventricular (LV) single cardiomyocytes were isolated, as previously described [14]. Tissue of both animal groups was fixed overnight with 2% glutaraldehyde in 0.05 M cacodylate buffer at 4°C for light microscopic (LM) and electron microscopic (EM) examination or were fixed overnight in 4% paraformaldehyde and transferred in 70% ethanol until embedded in paraffin.…”
Section: Animal Modelmentioning
confidence: 99%
“…Hearts were dissected and weighted. Single adult cardiomyocytes from the LV were obtained by enzymatic dissociation through retrograde perfusion of the aorta, as previously described [14]. The hearts were perfused with normal Tyrode (NT) (in mM, NaCl 137, KCl 5.4, MgCl 2 0.5, CaCl 2 1, Na-HEPES 11.8, glucose 10 and taurine 20; pH 7.35) on a Langendorff setup at 37°C.…”
Section: Cardiomyocyte Isolationmentioning
confidence: 99%
See 1 more Smart Citation